The role of nutrtion in children with celiac disease - Muzal Kadim (World Nutrition Journal, 2021)
Celiac disease, a permanent, irreversible but treatable disease  is an autoimmune disease triggered by gluten ingestion in genetically predisposed individuals, also known as celiac sprue and gluten sensitive enteropathy.  Recent findingsIntestinal inflammation and villous atrophy in small intestines by permanent intolerance to gluten in celiac disesea leads to seveare malabsorption. About 20%-38%  patients were basically nutritionally imbalance secondary malabsorption due to mucosal damage. Nutrition plays a very important role in the management of celiac disease. Gluten free diet must be balanced to cover nutrient requirements to prevent deficiencies and ensure children’s health, growth and development.Conclusion Gluten-free diet is the only accepted and available treatment in CD. It was a life-long treatment, if not carried out with attention, it may lead to nutritional imbalance which can affect children’s growth and development